THU0084 THE LONG-TERM OUTCOME OF INTRA-ARTICULAR GLUCOCORTICOID INJECTED JOINTS ON RADIOGRAPHIC CHANGES IN PATIENTS WITH RHEUMATOID ARTHRITIS: A REAL WORLD DATA FROM A SINGLE CENTER. (June 2019) - Koh, Jung Hee; Lee, Hanna; Kim, Ji-Won; Lee, Seung Geun
Abstract : Background: Intra-articular glucocorticoids injections (IAGI) have been an important part of a treat-to-target strategy in patients with Rheumatoid arthritis (RA). However, it is not known the long-term outcome of glucocorticoids-injected joint. Objectives: To explore the long-term outcome of IAGI, the impact on the radiographic joint space narrowing and erosion in patients with RA. Methods: We performed a retrospective cohort study of IAGI for patients with RA. We identified 88 RA patients who received IAGI into wrists or hand joints determined by ultrasound and had pre-injection and follow-up hand radiographs from a rheumatology department in a tertiary hospital. As a comparator, 88 RA patients who had not received IAGI although they had clinical synovitis (defined as both tender and swollen joint) in wrist or hand joint were randomly selected (Non-IAGI group). Hands radiographs scored using the van der Heijde-modified Sharp Score (HSS) method was used to assess radiographic progression (ΔHSS ≥ 1 in joint areas of synovitis). Multivariable Cox regression estimated the hazard ratio (HR) and 95% confidence interval (95% CI) for radiographic progression of joint with synovitis. Results: Among 88 RA patients who received IAGI (median age, 60 years, 42 (48%) patients had radiographic progression of triamcinolone-injected joint, while 38 patients (43%) in non-IAGI group (median age, 57 years) presented radiographic progression of joint area suffered clinical synovitis (not significant) in the median 2 years follow-up. At baseline, IAGI group presented longer disease duration, lower acute phase reactant levels and less involvement of proximal interphalangeal joints than non-IAGI group did. In the IAGI group, a median number of 1 (IQR, 1–2) joint was injected. After 3 months from IAGI, 63.5% of patients reported improvement of injected joint and 16.5% of patients received a second or more IAGI. The radiographic progression of injected joint (Figure 1 ) waspronounced at the wrists (87.8% of radiographic progressor). The level of C-reactive protein at active arthritis, baseline HSS and power Doppler grade in ultrasound was higher in radiographic progressor than in non-radiographic progressor. A high baseline HSS of hands (HR, 1.021 [95% CI, 1.002–1.040]), wrist joint involvement (HR, 5.356 [95% CI, 1.705–16.813]) and use of NSAIDs (HR, 0.373 [95% CI, 0.179–0.776]) were associated with radiographic progression in joint areas which suffered active synovitis. Conclusion: In patients with RA, IAGI did not have an additional effect on radiographic progression in the next 2 years. High baseline HSS and wrist joint involvement are independent risk factors of radiographic progression in joints suffered synovitis. References: [1] Hetland ML, Ostergaard M, Ejbjerg B, Jacobsen S, Stengaard-Pedersen K, Junker P, Lottenburger T, Hansen I, Andersen LS, Tarp U, et al: Short- and long-term efficacy of intra-articular injections with betamethasone as part of a treat-to-target strategy in early rheumatoid arthritis: impact of joint area, repeated injections, MRI findings, anti-CCP, IgM-RF and CRP. Annals of the rheumatic diseases 2012, 71(6):851-856. Acknowledgement: This research was supported by grants from the National Research Foundation of Korea (NRF) funded by the Ministry of Science and ICT (NRF-2018R1D1A1B07045491) Disclosure of Interests: None declared